Sesquiterpenos cariofilanos e outros constituintes químicos de Evolvulus linarioides MEISN. (Convolvulaceae) - Pereira, Laiane Caline Oliveira (2016)
The Convolvulaceae family consists 58 genera and approximately 1,880 species, known as morning glory and presenting a cosmopolitan distribution. In Brazil there are 22 genera and 403 species. Among the genera, Evolvulus stands out for presenting species with great unexplored potential from the phytochemical and pharmacological point of view, with several classes of metabolites and various uses in medicine popular proven. To conduct this study, the aerial parts of E. linarioides were submitted to extraction processes and chromatographic techniques. The structural characterization of isolated chemical components was performed by analysis of the spectral data of Infrared, nuclear magnetic resonance 1H and 13C, one- and two-dimensional, melting point and optical rotation. In the study were isolated from the hexane phase three substances, first reported in the species studied: ferulate alkyl (El-1); stigmasterol (El-2a) and β-sitosterol (El-2b), in a mixture. In addition to the sesquiterpene: 13α-acetoxy-4,5-epoxy-cariofilan-8β-ol (El-3), named evolfileno and 13α-acetoxy-3-cariofil(4)-en-8β-5α-diol (EI-4), to which was assigned the name acetate linariofileno, both unpublished literature. These results contributed to the knowledge of Evolvulus genera through the phytochemical study of E. linarioides since reported the isolation of three compounds reported for the first time for this kind of study and two unpublished sesquiterpenes in the literature as a natural product (evolfileno and acetate linariofileno).